Impact of post-traumatic stress disorder on epileptogenic networks: a functional connectivity study - Lisa-Dounia Soncin; Sara Simula; Nicolas Hemmer; Hélène Mourre; Marie Arthuis; Julia Makhalova; Christian Benar; Sylvane Faure; Fabrice Bartolomei (Scientific Reports)
Abstract Post-traumatic stress disorder (PTSD) is more common in patients with drug-resistant epilepsy. Some of these patients experience PTSD due to early psychotraumatic events. This study aims to assess the influence of PTSD on interictal functional connectivity using stereoelectroencephalography (SEEG) recordings in patients with temporal lobe DRE (TDRE). Two groups were considered: TDRE patients with PTSD (PTSD+, N = 11) and TDRE patients without PTSD (PTSD-, N = 12). All subjects had questionnaires measuring anxiety, depression, PTSD symptoms related to seizures, a diagnostic PTSD questionnaire, and a childhood trauma questionnaire. Resting state functional connectivity (FC) was evaluated on SEEG signals to analyze network characteristics. We mainly focused on brain regions involved in PTSD (amygdala, orbitofrontal cortex, hippocampus, insula, rhinal cortex, anterior cingulate cortex). Results revealed increased FC in PTSD + subjects in the brain regions involved in PTSD, but only in the hemisphere ipsilateral to the epileptogenic zone. In contrast, a decreased FC in the contralateral hemisphere was observed in the hippocampus. These findings support the existence of a PTSD-epilepsy-reinforced network, leading to FC alterations dependent on the epilepsy side and the region. Our study is the first to offer insights into the intricate dynamic linking PTSD and epilepsy and highlights the need for accounting for the influence of comorbidities on epileptogenic networks.